Study Literature: Application of The Principles of Thermodynamics, Thermal Expansion and Heat Transfer in Daily Life - Shofia, Amira; Khatimah, Sheylla Husnul; Maharani, Luthfiyyah; Putri, Salma Dewi; Rezki, Della Miftahul; Ersa, Putri Amalia; Yulianti, Weni; Chania, Zeli Afriani (Jurnal Fisika Papua, 2024)
Thermodynamics belongs to the group of physics that contains material about calories and their transfer. The concepts of thermodynamics, thermal accumulation, and heat transfer are not only found in everyday life, but the principles of thermodynamics are also used in the use of industrial tools and technologies. The purpose of this research is to find out the tools, fields, and any activity that uses the principles of thermodynamics, heat transfer, and fertilization in its application. This study uses a method of literature review by analyzing 30 relevant articles and focusing on the application of the principles of thermodynamics, thermal absorption, and heat transfer in life. The results of the study found that thermodynamics, thermal accumulation, and heat transfer play an important role in a variety of activities such as the manufacture of debris, wheat, plywood, and brick, as well as in the use of electronic devices such as refrigerators, hair dryers, and hand dryers. In addition, the principle of thermodynamics is applied in industrial technologies such as mini generators, steam power plants, and the ceramic industry. The results of this study show that the laws of thermodynamics are widely applied in various aspects of life, both on a domestic and industrial scale.